PELATIHAN PEMBUATAN PUPUK HAYATI DI KWT MANDIRI, PEKON GADING REJO UTARA, KECAMATAN GADING REJO, PRINGSEWU LAMPUNG - Yeni Yeni; Sekar Dwi Rizki; Ratih Rahhutami; Betari Safitri; Pebria Sisca; Brigitta Novena; Aditya Sukmawati (Jurnal Abdi Insani, 2025)
The village of Gading Rejo Utara, located in the Gading Rejo Subdistrict, is characterized by widespread agricultural land use, supported by naturally fertile soil conditions. A significant issue in the community is the improper management of wastewater generated from local, small-scale tofu production. This environmental challenge is directly linked to the limited availability of agricultural fertilizers. The community's primary fertilizer sources are government-subsidized products and animal manure, indicating a gap in local, sustainable production. This training initiative aimed to enhance the knowledge and practical skills of the 'Mandiri' Women Farmers Group (KWT) members in Gading Rejo Utara Village. The project focused on utilizing local resources, specifically tofu wastewater and abundant bamboo, for the production of biofertilizer. A total of 15 KWT 'Mandiri' members participated in the activity. The methodology employed was a participatory approach, comprising several stages: 1) initial observation to identify village resources; 2) a preparatory phase involving practical training on bamboo root bioactivator production; 3) implementation, which included knowledge- sharing discussions and a demonstration of organic fertilizer production using bamboo roots; and 4) monitoring and evaluation. Evaluation results indicated a significant increase in participant knowledge (60%), attitude (82.4%), and skills (81.78%). In conclusion, this community service intervention successfully enhanced the KWT members' knowledge regarding the potential of tofu wastewater for organic fertilizer production. It also fostered increased motivation among participants to independently produce organic fertilizer.